Pengalaman Wisatawan Mengikuti Cooking Class: Sebuah Studi Netnografi - Ida Ayu Sri Puspa Adi (JURNAL GASTRONOMI INDONESIA, 2023)
Netnography has increasingly gained interest among researchers in recent years because social interactions on the Internet are becoming increasingly intense. One of the social interactions that occur is tourists who express their experience of doing tourism activities. Therefore, this study aims to understand and analyze the experiences of tourists participating in cooking classes and their satisfaction. The data analyzed are tourist comments or testimonials on TravelAdvisor regarding “Traditional Balinese Cooking Class and Meal in a Multi-generational Family Home” taken on 23 February 2023. The data comes from tourist comments from 1 October 2022 to 23 February 2023 and the number of comments analyzed was 42. The results showed that the tourists who took part in the cooking class were satisfied where all of them gave a maximum rating of 5. They felt that this activity was a very enjoyable experience so it is highly recommended to participate. In addition, tourists feel that these activities show the culture of the Balinese people, delicious Balinese cuisine, Balinese hospitality, authentic experiences, feeling they are learning new things and their intention to return back to the activity.